Treatment of neovascular age-related macular degeneration with anti-VEGF agents: retrospective analysis of 5-year outcomes - Pedrosa AC (Dove Medical Press, 2016)
Ana Catarina Pedrosa,1 Adriana Reis-Silva,2 João Pinheiro-Costa,1,3 João Beato,1 Paulo Freitas-da-Costa,1,3 Manuel S Falcão,1,2 Fernando Falcão-Reis,1,2 Ângela Carneiro1,2 1Department of Ophthalmology, Hospital de São João, 2Department of Sense Organs, 3Department of Anatomy, Faculty of Medicine, University of Porto, Porto, Portugal Purpose: To evaluate the 5-year results obtained in clinical practice in the treatment of neovascular age-related macular degeneration (nAMD) with anti-VEGF agents.  Materials and methods: We retrospectively analyzed all patients with nAMD who initiated anti-VEGF treatment before October 2009. We collected data regarding visual and anatomical outcomes.  Results: A total of 278 patients met the selection criteria. The mean number of intravitreal injections was 5.7 in the first year and 3.7 in the fifth year. A positive mean visual acuity variation of +3.7 Early Treatment Diabetic Retinopathy Study letters occurred in the first year, but no significant differences relative to baseline were observed thereafter. The majority of patients (71%) maintained stable visual acuity throughout follow-up. At 5 years, mean central macular thickness remained substantially inferior to baseline (-96.6 µm), and 56% of patients maintained dry retinas.  Conclusion: Anti-VEGF therapy leads to long-term visual stabilization in the great majority of patients. Keywords: age-related macular degeneration, choroidal neovascularization, vascular endothelial growth factor, visual acuity